An Analysis of Graduate Theses Based on Watson’s Human Caring Model in Nursing - Cemal Özalp (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: The aim of this review is to examine the postgraduate theses based on Watson's Human Care Model in the field of nursing in Türkiye.Materials and Methods: Within the scope of the review, theses registered in the National Thesis Centre were scanned with the keywords ‘Watson’ and ‘human care’ in Türkiye between 1-15 December 2024. The theses were analyzed in terms of application group, sample, method, research type and results.Results: It was determined that 28 theses in the field of nursing in Türkiye included studies based on Watson's Human Care Model. Of these theses, 7.15% were master's theses, 92.85% were doctoral theses and 53.57% were randomized controlled trials. When the theses based on Watson's Human Care Model were analyzed according to years, it was determined that 17.86% of them were written in 2022. In addition, 57.14% of the postgraduate theses based on Watson's Human Care Model were in the department of nursing. In graduate theses based on Watson’s Human Caring Model, studies primarily focused on female patients, cancer and terminal patients, children, and the elderly, as well as nurses and healthcare professionals. The findings indicate that various approaches have been developed for both patient care and the practices of healthcare professionals.Conclusion: The majority of postgraduate theses based on Watson’s Human Caring Model were doctoral studies conducted mainly in nursing departments, with randomized controlled trials being the most commonly used method. The studies focused on various patient groups, including women, children, adolescents, the elderly, cancer and terminal patients, as well as healthcare professionals, highlighting the development of diverse approaches for both patient care and nursing practice.